SY08-2NEUROPHYSIOLOGICAL AND NEUROIMAGING ASPECTS BETWEEN INTERNET GAMING DISORDER AND ALCOHOL USE DISORDER. (September 2014) - Choi, J. S.
Abstract : Introduction. Internet Gaming Disorder (IGD) causes significant public mental health problems worldwide, especially in Korea. It is important to compare characteristics of IGD with those of substance addiction in order to elucidate the pathophysiology of IGD. In this study, we explored the neurophysiological and neuroimaging features among patients with IGD and those with Alcohol Use Disorder (AUD). Method. First, we performed resting-state EEG in male patients with IGD (N = 20) and compared the results with those of male patients with AUD (N = 20) and healthy controls (N = 20). All patients were seeking treatment at our clinics due to their excessive Internet game use or alcohol drinking. Second, we performed resting-state functional MRI study in same subjects. However, some subjects were excluded in the analysis due to their motion artifacts. Sixteen male patients with IGD, 14 male patients with AUD, and 15 healthy male controls were included in the final analysis. Result. Patients with IGD showed decreased beta activity compared with those with healthy controls, whereas patients with AUD showed increased beta activity compared with those with healthy controls. In addition, both clinical groups showed decreased delta activity compared with those with healthy controls. In the resting-state fMRI, IGD group showed a significant regional homogeneity (ReHo) decrease in the right superior temporal gyrus (STG) and increase in the posterior cingulate cortex (PCC) compared with healthy controls. AUD group showed significant decrease in the anterior cingulate cortex (ACC) and increase in the PCC compared with healthy controls. Conclusion. These results showed neurobiological similarity and disparity of resting-state EEG and fMRI features among IGD, AUD and healthy controls. These findings may contribute to elucidate the pathogenesis and neurobiological underpinning of IGD.